1990
DOI: 10.1007/bf00117476
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of nonsmoking women to environmental tobacco smoke: a 10-country collaborative study

Abstract: The interpretation and interpretability of epidemiologic studies of environmental tobacco smoke (ETS) depend largely on the validity of self-reported exposure. To investigate to what extent questionnaires can indicate exposure levels to ETS, an international study was conducted in 13 centers located in 10 countries, and 1,369 nonsmoking women were interviewed. The present paper describes the results of the analysis of self-reported recent exposure to ETS from any source in relation to urinary concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 15 publications
(6 reference statements)
5
74
0
1
Order By: Relevance
“…We did not collect ETS data in the detail that some studies designed exclusively to evaluate passive smoking have. However, a key strength of our study is that we did systematically collect lifetime ETS information for the 2 sources most relevant in previous biomarker studies 32,33 and collected them for each residence and job.…”
Section: Resultsmentioning
confidence: 99%
“…We did not collect ETS data in the detail that some studies designed exclusively to evaluate passive smoking have. However, a key strength of our study is that we did systematically collect lifetime ETS information for the 2 sources most relevant in previous biomarker studies 32,33 and collected them for each residence and job.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the available data, a categorization of saliva cotinine concentrations into four groups was suggested: 1) undetectable cotinine is associated with the absence of active or passive smoking; 2) cotinine concentrations <10 ng·mL -1 usually result from exposure to ETS without active smoking; 3) cotinine concentrations ranging 10-100 ng·mL -1 usually result from infrequent active smoking or regular active smoking with low nicotine intake, but heavy passive exposure to tobacco smoke can result in levels ≥10 ng·mL -1 ; and 4) levels >100 ng·mL -1 are the result of regular active smoking [63]. Detectable cotinine levels have been measured in 80-91% of the samples in different studies, and ETS exposure has been shown to take place at home, in the workplace and in a number of other settings [3,4,6,7]. In addition to plasma, saliva and urine, cotinine has also been detected in cervical fluid of women exposed to ETS [64] and in semen of men reporting ETS exposure [65].…”
Section: Biomarkersmentioning
confidence: 99%
“…For example, among adult populations the mean urinary cotinine concentrations have been shown to increase with the degree of selfreported exposure [66], and with the number of selfreported exposures to ETS during the previous 4 days, as shown in figure 5 [3]. Among nonsmoking women in a 10-country collaborative study, urinary cotinine/creatinine levels rose with self-reported ETS exposure from no exposure through exposure at work alone and exposure only at home, to exposure both at home and at work [4]. The results of a linear regression analysis indicated that reported duration of ETS exposure and the number of cigarettes to which the subject reported being exposed were strongly related to the urinary cotinine level.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that determine exposure using a biomarker are more difficult to conduct and more expensive than questionnaire data. Studies have examined the agreement between self -reported ETS exposure and biochemical markers of ETS exposure (Coultas et al, 1988;Coultas et al, 1989;Coghlin et al, 1989;Haley et al, 1989;Riboli et al, 1990;Becher et al, 1992;Emmons et al, 1994;Kemmeren et al, 1994), and a few have examined this association in pregnant women (O'Connor et al, 1995;Rebagliato et al, 1995b ). However, the analytic methods used to determine biochemical markers of ETS exposure in many of these studies were not as sensitive as can be obtained currently.…”
Section: Introductionmentioning
confidence: 99%